2016
DOI: 10.1186/s12889-016-3899-7
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the effectiveness of health warning labels on smokeless tobacco products in four states in India: findings from the TCP India cohort survey

Abstract: BackgroundIn 2009, after many delays and changes, India introduced a single pictorial health warning label (HWL) on smokeless tobacco (SLT) packing—a symbolic image of a scorpion covering 40% of the front surface. In 2011, the scorpion was replaced with 4 graphic images. This paper tested the effectiveness of SLT HWLs in India and whether the 2011 change from symbolic to graphic images increased their effectiveness.MethodsData were from a cohort of 4733 adult SLT users (age15+) of the Tobacco Control Project (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 26 publications
(29 reference statements)
0
32
0
Order By: Relevance
“…Previous research has reported that there is a diminished effect of cognitive processing of graphic health‐warning labels on participants after 5 years, indicating the need for a regular refreshment of graphics . A study in India showed that graphics on cigarette packaging is strongly effective in increasing awareness, but not effective enough to motivate them to quit . Current health education is not sufficient to achieve behavioral changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has reported that there is a diminished effect of cognitive processing of graphic health‐warning labels on participants after 5 years, indicating the need for a regular refreshment of graphics . A study in India showed that graphics on cigarette packaging is strongly effective in increasing awareness, but not effective enough to motivate them to quit . Current health education is not sufficient to achieve behavioral changes.…”
Section: Discussionmentioning
confidence: 99%
“…31 A study in India showed that graphics on cigarette packaging is strongly effective in increasing awareness, but not effective enough to motivate them to quit. 32 Current health education is not sufficient to achieve behavioral changes. Interventional studies are needed using a primary healthcare approach focused on smokers, with adequate follow up.…”
Section: Discussionmentioning
confidence: 99%
“…This study confirms low level of noticing and effectiveness reported in other Indian studies. 27,28 Additionally, change from the symbolic warnings (before COTPA) to graphics health warnings (after COTPA) did not lead to increase in noticing as well as effectiveness.…”
Section: Discussionmentioning
confidence: 90%
“…Tobacco control policies compliance decreased smoking prevalence. 19,[21][22][23]26,28 A policy on tobacco sale to minor was associated with lowering youth smoking. 22 Although the laws clearly prohibit the sale of tobacco products to young people <18 of age in India, 8 the current study shows initiation of tobacco use continues to starts as early as 9 years or younger.…”
Section: Discussionmentioning
confidence: 99%
“…Despite numerous delays in implementation (Arora, Tewari, Nazar, Gupta & Shrivastav, 2012; Oswal, Raute, Pednekar, & Gupta, 2011), in 2009, India became the first country in the world to require pictorial health warnings (a symbolic image of a scorpion) on smokeless tobacco packages. In 2011, the symbolic image of a scorpion was replaced with four different graphic images, but recent longitudinal evidence indicated that this change from a symbolic warning in 2009, to graphic warnings in 2011, did not result in significant increases in effectiveness (Gravely et al, 2016). However, India has committed to increasing warning size from the current 40% of the front surface to 85% of the principal display area (i.e., front and back).…”
Section: Introductionmentioning
confidence: 99%